Cuius Regio? Ideological and Territorial Cohesion of the Historical Region of Silesia (c. 1000-2000) vol. 4. Region divided. Times of nation-states (1918-1945) - Wiszewski, Przemysław; Czapliński, Marek; Greiner, Piotr (Wydawnictwo eBooki.com.pl, 2014)
This book is a collection of articles devoted to the cohesion of Silesia as a region in the years 1918–1945. Their role is to conclude the studies conducted as part of another stage of the European Science Foundation’s programme entitled Cuius regio. An analysis of the cohesive and disruptive forces determining the attachment and commitment of (groups of) persons to and the cohesion within regions. The authors of the studies have attempted to analyse the functioning of five basic factors which determined the region's coherence. In line with the themes of the project as a whole, these are: the administrative framework (Tomasz Kruszewski), the economy (Miron Urbaniak), social groups (Tomasz Przerwa), ethnic issues (Grzegorz Strauchold) and the cultural identity of the region’s inhabitants (Bernard Linek). A special difficulty for the historians was posed by the necessity to trace the issues of their interest in the realities of three countries (Czechoslovakia, Germany and Poland), whose functioning was at that time founded on national ideologies which strongly opposed regionalisms. Such an approach made it possible to identify phenomena on a scale much larger than those which were determined by the political activity of elites of a single country only. Above all, however, it made it possible for them to answer the question of whether the sense of being part of regional and local communities was transformed under the influence of political and ideological changes spreading through the whole of Central Europe, as well as the extent to which they resulted in Silesia surviving as a region or disintegrating into three provinces of three nation-states.
Keywords: Silesia; social cohesion; regional history